Analysis of Key Audit Matters Disclosures in Financial Reporting: The First Evidence from Indonesia - Batara, Gamal; Jalaluddin, Jalaluddin; Yahya, M. Rizal (Universitas Padjadjaran, 2024)
The aim of this study is to explore the first year of Key Audit Matters (KAMs) disclosure in Indonesia, which has been fully adopted since 2022. The research reports on matters published in 806 statutory audit reports of listed companies in 2022. This study provides the first description of KAMs disclosure by Indonesian public companies. The findings suggest that the most common KAM disclosures are related to